Economic evaluation of Piaractus mesopotamicus juvenile production in different rearing systems - Jomori, Rosangela Kiyoko [UNESP]; Carneiro, Dalton José [UNESP]; Martins, Maria Inez Espagnoli Geraldo [UNESP]; Portella, Maria Célia [UNESP] (Elsevier, 2005)
In this study, the costs and gross income related to the production of pacu Piaractus mesopotamicus juveniles were evaluated. This evaluation took into consideration a semi-intensive rearing, with direct stocking of the larvae into fertilized ponds (IL 0), or an initial intensive larviculture system, in which the larvae were fed in the laboratory for 3 (IL 3), 6 (IL 6), or 9 days (IL 9) before being transferred to the ponds. After 45 days of rearing, a gradual increase in production costs was observed as intensive larviculture time increased. Gross income also increased due to better survival rates (11.0, 25.3, 45.4, and 54.0% for IL 0, IL 3, IL 6, and IL 9, respectively). Therefore, increased profits were obtained under intensive larviculture (US$ 0.27, US$ 6.07, US$ 11.99, and US$ 13.16 per one thousand larvae in treatments IL 0, IL 3, IL 6, and IL 9, respectively). In a larger scale production simulation, the results obtained with initial intensive larviculture also showed evident economic advantages, confirming the feasibility of this system in comparison with the direct stocking of larvae in ponds for the production of pacu juveniles. © 2004 Elsevier B.V. All rights reserved.
Keywords: Economic feasibility; Intensive rearing system; Juvenile rearing; Larviculture; Pacu; Semi-intensive rearing system; aquaculture production; aquaculture system; cost-benefit analysis; feasibility study; fishery economics; income; Piaractus; Piaractus mesopotamicus